Mitigation of Heavy Metals from Different Industrial Effluents Using Different Nano-particles - Sriram Bharadwaj*, N.; Sudarshan, J.; Prasanna, K.; Singh, Namrata (Asian Journal of Chemistry, 2013)
Present times have seen an accelerated growth of pollution of water resources due to anthropogenic activities especially industrial processes and household agricultural waste. This has caused tremendous public concern due to its environmental implications. Wastewaters from many industrial processes such as metal plating and finishing processes contain a variety of chemicals like alkaline and acid cleaners, electrocleaners and pickling solutions. These solutions are often laden with metal ions and can rarely be treated biologically. Conventional physical/chemical wastewater treatment technologies for metal removal used industrially, such as hydroxide or sulfide precipitation, evaporation and ion exchange, are effective for most wastes but result in hazardous waste sludge's requiring costly removal. The use of zero-valent iron, magnetite and titanium dioxide nanoparticles as a reductive medium are receiving increased interest due to low operation and maintenance costs. In addition, it is easy-to-obtain, with good effectiveness and ability for degrading contaminants. Efforts in this project is to opt simplest and cost effective methods for synthesis of three nanoparticles (zero valent iron, Fe3O4, TiO2) and to check their efficiency in three different effluents having different wastewater characteristics for the removal of heavy metals as chromium, cadmium and lead. Through our paper we would demonstrate that TiO2 is the best; showing maximum efficiency in the removal of heavy metals from different effluents as TiO2 has an efficiency of over 96 % removal of Cr, Cd and Pb impurities from the polluted water.